South-Western Federal Taxation 2021: Essentials of Taxation: Individuals and Business Entities, 24th Edition - Annette Nellen; Andrew D. Cuccia; Mark Persellin (Cengage Learning, 2020)
Gain an understanding of today's tax concepts and ever-changing laws with the concise, reader-friendly SOUTH-WESTERN FEDERAL TAXATION 2021: ESSENTIALS OF TAXATION: INDIVIDUALS AND BUSINESS ENTITIES, 24E. Master key taxation concepts and applications you need for success in accounting and taxation or prepare to take the C.P.A. or Enrolled Agent Exam. With this edition you examine the most current tax law at the time of publication, from recent tax law changes to complete coverage of the Tax Cuts and Jobs Act of 2017 with related guidance from the Treasury Department. Concise coverage highlights the most important rules and concepts on income, deductions and losses, property transactions, business entities, multi-jurisdictional taxation, as well as taxes on financial statements. Clear and numerous examples, helpful summaries and interesting tax scenarios further clarify concepts and help you sharpen your critical-thinking, writing and research skills. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.